Factors affecting commencement and cessation of betel quid chewing behaviour in Malaysian adults - Handa Yujiro; Gupta Prakash C; Axell Tony; Ikeda Noriaki; Talib Norain A; Yang Yi-Hsin; Razak Ishak A; Ghani Wan MN; Abdullah Norlida; Zain Rosnah B (BMC, 2011)
Abstract Background Betel quid chewing is a common habit widely practiced in Southern Asian populations. However, variations are seen in the content of a betel quid across the different countries. Factors associated with commencement and cessation of this habit has been numerously studied. Unfortunately, data on Malaysian population is non-existent. This study aims to determine the factors associated with the inception and also cessation of betel quid chewing behaviour among Malaysian adults. Method This study is part of a nationwide survey on oral mucosal lesions carried out among 11,697 adults in all fourteen states in Malaysia. The questionnaire included sociodemographic information and details on betel quid chewing habit such as duration, type and frequency. The Kaplan-Meier estimates were calculated and plotted to compare the rates for the commencement and cessation of betel quid chewing behaviour. Cox proportional hazard regression models were used to calculate the hazard rate ratios for factors related to commencement or cessation of this habit. Results Of the total subjects, 8.2% were found to be betel quid chewers. This habit was more prevalent among females and, in terms of ethnicity, among the Indians and the Indigenous people of Sabah and Sarawak. Cessation of this habit was more commonly seen among males and the Chinese. Females were found to be significantly more likely to start (p < 0.0001) and less likely to stop the quid chewing habit. Females, those over 40 years old, Indians and a history of smoking was found to significantly increase the likelihood of developing a quid chewing habit (p < 0.0001). However, those who had stopped smoking were found to be significantly more likely to promote stopping the habit (p = 0.0064). Cessation was also more likely to be seen among those who chewed less than 5 quids per day (p < 0.05) and less likely to be seen among those who included areca nut and tobacco in their quid (p < 0.0001). Conclusion Factors that influence the development and cessation of this behaviour are gender, age, ethnicity, and also history of smoking habit while frequency and type of quid chewed are important factors for cessation of this habit.